Employee motivation: a Malaysian perspective - Islam, Rafikul; Ismail, Ahmad Zaki (Emerald Group Publishing Limited, 2008)
It is a challenging task for managers to keep employees motivated in their works in order to achieve the organizational goals. Due to the varied nature of human beings, a factor that can motivate someone, may not do so in others. Therefore, it is important for managers to know the ‘exact’ motivators for his/her employees. The present research intends to find out the effective motivators to the employees working in various Malaysian organizations. A list comprising ten motivators has been prepared and the items in the list are prioritized by taking inputs from 505 employees working in more than 96 various public and private organizations in Malaysia. The findings of the research are expected to provide guidelines in developing an appropriate motivational program across organizations, particularly Malaysian organizations.